The effect of health insurance on workers' compensation filing: Evidence from the affordable care act's age-based threshold for dependent coverage - Marcus Dillender (W.E. Upjohn Institute for Employment Research, 2015)
This paper identifies the effect of health insurance on workers' compensation (WC) filing for young adults by implementing a regression discontinuity design using WC medical claims data from Texas. The results suggest health insurance factors into the decision to have WC pay for discretionary care. The implied instrumental variables estimates suggest a 10 percentage point decrease in health insurance coverage increases WC bills by 15.3 percent. Despite the large impact of health insurance on the number of WC bills, the additional cost to WC at age 26 appears to be small as most of the increase comes from small bills.
Keywords: I13; J32; J38; 330; Workers' compensation; Moral hazard; Health insurance; Affordable Care Act